Enhanced Efficacy of Some Antibiotics in Presence of Silver Nanoparticles Against Multidrug Resistant Pseudomonas aeruginosa Recovered From Burn Wound Infections - Khalil, Maha A.; El Maghraby, Gamal M.; Sonbol, Fatma I.; Allam, Nanis G.; Ateya, Perihan S.; Ali, Sameh S. (Frontiers in Microbiology, 2021)
Burn wound infections with multidrug-resistant (MDR) bacteria are shown in many countries as severe widespread health threats. Consequently, attention has been devoted to new nanoparticle-based materials in the field of antimicrobial chemotherapy of burn wound infections. This study aimed to evaluate both in vitro and in vivo efficacies of nanoparticle–antibiotic combinations as new classes of materials subjected against MDR Pseudomonas aeruginosa. Out of 40 Gram-negative isolates, 23 P. aeruginosa were recovered from patients with burn wound infections attending different hospitals in Tanta, Egypt. The susceptibility test revealed that 95.7% of P. aeruginosa isolates were MDR with a high incidence of resistance against carbenicillin. Antibacterial activities of silver nanoparticles (Ag-NPs) against the isolates examined showed various inhibition zone diameters ranging from 11 mm to 17 mm. Strong synergistic efficacy of neomycin was reported in combination with Ag-NPs against MDR P. aeruginosa P8 and P14 isolates. The in vivo effectiveness of various pharmaceutical formulations prepared from a combination of neomycin antibiotic with Ag-NPs in the treatment of induced bacterially infected mice burns showed that maximum healing activity along with faster wound contraction reported with the combination of neomycin-Ag-NPs in the spray formulation. Generally, data indicated that incorporating Ag-NPs in combination with certain antibiotics may be a new, promising application for wound treatments, especially burns infected with MDR P. aeruginosa.